ENHANCING ONLINE AUTOMOTIVE SPARE PARTS SALES THROUGH A WEB-BASED E-SALES SYSTEM USING RAPID APPLICATION DEVELOPMENT - Muhammad Alif Fiqri Harahap; Marina Elsera (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
The rapid advancement of information and communication technology has encouraged business sectors to adopt internet-based systems to improve operational efficiency and competitiveness. In the automotive industry, particularly in the sale of used car spare parts, electronic sales (e-sales) have become an important solution for expanding market reach and facilitating transactions. However, this sector still faces several challenges, including limited product transparency, inconsistent stock management, unclear product conditions, and low consumer trust in online transactions. This study aims to develop a web-based e-sales system for used car spare parts using the Rapid Application Development (RAD) method to improve transaction efficiency, inventory management, and customer trust. The RAD approach was selected because it emphasizes rapid and iterative system development through continuous prototyping and active user involvement, allowing applications to be developed according to user needs in a shorter time. The research method consisted of four stages: requirements planning, user design, construction, and implementation. The resulting system integrates various functionalities, including product management, automatic inventory monitoring, customer registration and login, transaction processing, shipment tracking, website settings, and sales monitoring through an admin dashboard. The implementation results indicate that the developed system effectively improves operational efficiency by reducing manual recording activities and simplifying transaction management. Additionally, the system enhances transparency through detailed product information and transaction monitoring features, thereby increasing consumer confidence in purchasing used spare parts online. Overall, the implementation of the RAD method proved effective in developing an adaptive and efficient e-sales platform that supports digital transformation in the automotive spare parts.